A Model of Integrated Marketing Communication for Community Products: “Chi-Hot” Parsley Balm of Klong Yong Sub-district, Nakhon Pathom, Thailand - PAIROA , Isari; THIENTHAWORN, Ekapon (Journal of Ecohumanism, 2024)
Introduction: Herbal products are famous for their affordability, ease of production, and health benefits. People are more aware of their health. The biennial fragrant plant parsley has essential oils that can be used for various applications. It is extracted for inhaler balms under the brand “Chi-hot” (“Chi” is parsley in the Thai language). Purpose: This research aims to explore consumer behavior of herbal balm and develop an integrated marketing communication (IMC) model for selling parsley balm. Methods: This survey collects data by questionnaire from 256 consumers selected by convenient sampling method. Descriptive and inferential statistics analyzed the data. Findings: 78% of respondents have used herbal balm, and 48% purchase 1-2 times/month. The reasons for purchase are Price (38%), Brand(26%), and Quality (11%). IMC's model for selling parsley balm consists of Public Relations, Word-of-Mouth Marketing, Event Marketing, Advertising, Direct Marketing, Promotions, and Personal Selling. Implication: Parsley balm can be developed as a community herbal product to promote local wisdom and enhance local revenue. IMC's model of Public Relations, Word-of-Mouth Marketing, Event Marketing, Advertising, Direct Marketing, Promotions, and Personal Selling is effective for selling herbal products. Local manufacturers can employ this model easily with low investment.